Development of natural fiber‐reinforced plastics (NFRP) based on biobased polyethylene and waste fibers from Posidonia oceanica seaweed. Issue 8 (19th April 2014) - Ferrero, B.; Fombuena, V.; Fenollar, O.; Boronat, T.; Balart, R.
<x xml:space="preserve">Abstract</x> In the present study the valorization of wastes from Posidonia oceanica (PO) has been carried out in order to obtain a fully biobased composite material in combination with a biobased polyethylene obtained from sugar cane as matrix. Morphological analysis by scanning electron microscopy (SEM) of the fractured surfaces from impact tests has revealed a homogenous distribution of particles of PO, as a consequence, good balanced properties have been obtained for composites with PO contents in the 5–40 wt%. Thermal properties of composites have been studied through differential scanning calorimetry (DSC) and thermogravymetric analysis (TGA); the obtained results show an improvement on the thermal degradation. With regard to thermomechanical properties, dynamic mechanical analysis (DMA) results have shown a much enhanced storage modulus (G′) as the Posidonia oceanica content increases. Tensile tests have shown a remarkable increase in stiffness with tensile modulus values about 60% higher for composites with 40 wt% with regard to unfilled material. In a similar way, the flexural modulus is more than twice with regard the unloaded polyethylene. Shore D hardness confirms this improvement on mechanical properties and Charpy impact test shows values very similar to sample without PO, so that the intrinsic high impact energy absorption of HDPE is maintained in HDPE‐PO composites. The water uptake test determines that the water absorption percent does not exceed 8%, which is relatively low for a high immersion time (5 months), which guarantees a dimensional stability in lifetime for these composites. POLYM. COMPOS., 36:1378–1385, 2015. © 2014 Society of Plastics Engineers